Women and white-collar crime - Dodge, Mary (Prentice Hall's women and white-collar crime, 2009)
Traditions of masculinity -- From pink to white-collar crime : the case of embezzlement -- When opportunity knocks : women who commit white-collar crime -- Positions of political power -- Corporate crimes against women -- Professional deviance : occupational crimes against and by women -- Detecting white-collar crime : women as whistle-blowers -- Great expectations